Improving the Methods of Treatment and Prevention of Complications of Odontogenic Diseases of the Jaws in Children - Kamolova Feruza Rahmatilloyevna; Qalandarov Eldor Shermat ugli (Genius Journals, 2022)
Treatment and prevention of inflammatory diseases of the maxillofacial region are one of the main problems of pediatric dentistry. According to a number of researchers, inflammatory diseases of the maxillofacial region account for up to 21% of all surgical and 52% of dental diseases in childhood. In most children, the source of odontogenic inflammatory diseases are complications of caries of temporary teeth. Depending on the nature of the pathogen and the reaction of the child's body, ways of infection, etc., inflammatory diseases in the maxillofacial region can be both acute and chronic
Keywords: odontogenic diseases; causative tooth; prevention; oral cavity